PENINGKATAN MOTIVASI DAN HASIL BELAJAR IPA MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM ASSISTED INDIVIDUALIZATION (TAI) SISWA KELAS VIIC SMP TAMAN DEWASA IBU PAWIYATAN YOGYAKARTA - Desma Eryanti (N A T U R A L: Jurnal Ilmiah Pendidikan IPA, 2016)
The purpose of this research is to improve students motivation and science learning outcomes VIIC grade students through cooperative learning model Team Assisted Individualization (TAI) in the SMP Taman Dewasa Ibu Pawiyatan Yogyakarta 2013/2014 school year. This type of research is Classroom Action Research (CAR), which is done collaboratively. The subjects in this study were junior high school students of class VIIC SMP Taman Dewasa Ibu Pawiyatan Yogyakarta totaling 29 students. The object of this research is to use the model of learning with Team Assisted Individualization (TAI), motivation, and student learning outcomes. Data collection techniques in this study were done by observation, interviews, documentation, and testing. The results showed that after application of the model Team Assisted Individualization (TAI) in the junior class VIIC SMP Taman Dewasa IbuÂ  Pawiyatan Yogyakarta, motivation and learning outcomes IPA increased. This is shown by an increase in the average yield percentage of observations of students motivation for each cycle, the average indicator of motivation in the first cycle is 85.31% and increased 6.19% to 91.50% in the second cycle. The average results of students in science learning at pre-action 46.72 to 51.37 in the first cycle and became 77.24 in the second cycle. Many students who achieve KKM also increased. In the first cycle, there are seven students who achieve KKM KKM and attainment percentage of 24%, while in the second cycle can be increased to 23 and the percentage of students achieving 79% KKM.